Dispersal and individual variability: laboratory experiments with the woodlouse Porcellio scaber - Uchmański, Janusz; Opaliński, Krzysztof W.; Rau, Karolina; Uvarov, Alexei V. (Studia Ecologiae et Bioethicae, 2017)
Laboratory experiments on the dispersal of woodlouse Porcellio scaber showed that the possibility to disperse diminished the intensity of intraspecific competition. The decision to disperse from local habitat to another one didn’t depend on the weight of individual. The only category of individuals that tried to avoid dispersal were females carrying eggs. This can be connected with the Brownian way of movement of woodlouse during penetration of surrounding environment or with the arrangement of the experiment in which the costs of dispersal were low.